Word Power Made Easy : The Complete Handbook for Building a Superior Vocabulary - Lewis, Norman 1912-2006 (New York Pocket Books, 1948)
[This book offers] eliminate outmoded references and to reflect current idioms ... It teaches ideas and a method of broadening knowledge as an integral part of the vocabulary building process
Keywords: Vocabulary